The perfume garden [large type] - Brown, Kate Lord (Thorndike Press, 2015)
"High in the hills of Valencia, a forgotten house guards its secrets. Untouched since Franco's forces tore through Spain in 1936, the whitewashed walls have crumbled, and the garden, laden with orange blossom, grows wild. Emma Temple is the first to unlock its doors in seventy years. Emma is London's leading perfumier, but her blessed life has taken a difficult turn. Emma's free-spirited mother, Liberty, who taught her the art of fragrance making, has just passed away. At the same time, Emma has separated from her long-time lover and business partner, Joe, whose baby she happens to be carrying. While Joe is in New York trying to sell his majority share in their company, Emma, guided by a series of letters and a key bequeathed to her in Liberty's will, decides to leave her job and travel to Valencia, to the house her mother mysteriously purchased just before her death. Emma makes it her mission to restore the place to its former glory. But for her aging grandmother, Freya, a British nurse who stayed in Valencia during Spain's devastating civil war, Emma's new home evokes memories of a terrible secret, a part of her family's past that until now has managed to stay hidden. With two beautifully interwoven narratives and a lush, atmospheric setting, The Perfume Garden is a dramatic, emotional debut that readers won't soon forget"--